Recent Progress of Graphene-Based Photoelectrode Materials for Dye-Sensitized Solar Cells - Kaustubh Patil; Soheil Rashidi; Hui Wang; Wei Wei (International Journal of Photoenergy)
Graphite with a single atomic layer known as graphene shows great capability in energy conversion and storage devices. Dye-sensitized solar cells (DSSCs) have attracted intense interests due to offering high photo-to-electric conversion efficiencies. DSSCs are built from a photoelectrode (a dye-sensitized nanocrystalline semiconductor), an electrolyte with redox couples, and a counterelectrode. In this review article, we outline the strategies to enhance the efficiency and reduce the cost by introducing graphene into the DSSCs as the photoelectrode. First, the development of DSSCs and the properties of graphene are briefly described. Then, the applications of graphene-based materials for photoelectrodes (transparent electrode, semiconductor layer, and dye sensitizer) in DSSCs are deeply discussed. Finally, an outlook for graphene materials in DSSCs is provided.